Remediation of Soils Contaminated by Fluoride Using a Fermentation Product of Seaweed (Eucheuma cottonii) - Ruth Lorivi Moirana; Josephine Mkunda; Marcos Paradelo; Revocatus Machunda; Kelvin Mtei (Applied and Environmental Soil Science)
This study investigated the efficacy of fermented seaweed (Eucheuma cottonii) on the remediation of fluoride-contaminated soil. The soil was amended with either 1.25, 3.0, or 5.0% (w/w) fermented seaweed (FSW), parallel with the controls (0%). The amendment improved the physicochemical properties of the soil particularly pH regulated from strong alkaline (9.3) to neutral (7.0) which is essential for germination, crop growth, and yield. The amount of water soluble-fluoride (Ws-F) dropped from 81.7 ± 3.1 mg/kg to 42.7 ± 2.4, 33.7 ± 1.2, 19.6 ± 0.9, and 12 ± 1.3 mg/kg following 0, 1.25, 3, and 5% amendment dosage, respectively. Most of the Ws-F was converted into exchangeable fluoride (Ex-F) and to fluoride-bound to iron and manganese (Fe/Mn-F). Furthermore, the amendment also enhanced microbial mass and diversity in the soil. The FSW contains organic acids which participate in ionic bonding with the multivalent cations in the soil. The formed compound participates in ion exchange with clay or with anionic adsorption to positively charged clay sites at the edges. This interaction is further essential for enhancing the fluoride holding capacity of the soil. The use of seaweed reduced the bioavailability of fluoride in the agricultural soils and had positive effects on promoting soil fertility. However, further studies to observe its effects on crop performance is of significance.